1970
DOI: 10.3329/jdmc.v19i1.6253
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesaemia in Pregnancy: A predictor of Preterm Labour

Abstract: Preterm birth is a major health concern. It is the leading cause of perinatal mortality and morbidity. Besides varied etiology, it may be due to alteration in basic biochemical function of the body at cellular level stating emphasis to trace elements of which magnesium, being one of them. Pregnancy is marked by a state of hypomagnesaemia and varied hypomagnesaemia is observed in preterm labour cases. The study is conducted to find out the relationship between low serum magnesium concentrations with preterm lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 3 publications
8
16
3
Order By: Relevance
“…16 In this study, the age of the women, their parity, history of miscarriages and employment status were comparable in study and control groups, which exclude their effect on the result; similar to Kamal's et al and Shahid et al findings. 17,18 The number of preterm labour cases belong to lower socioeconomic class was significantly higher than high or middle classes, the same as Sharma A et al findings. 19 On the contrary Khani et al demonstrated non-significant increase in preterm labour among low socioeconomic class women may be due to the smaller sample size in his study when he took only 40 pregnant women.…”
Section: Discussionsupporting
confidence: 79%
“…16 In this study, the age of the women, their parity, history of miscarriages and employment status were comparable in study and control groups, which exclude their effect on the result; similar to Kamal's et al and Shahid et al findings. 17,18 The number of preterm labour cases belong to lower socioeconomic class was significantly higher than high or middle classes, the same as Sharma A et al findings. 19 On the contrary Khani et al demonstrated non-significant increase in preterm labour among low socioeconomic class women may be due to the smaller sample size in his study when he took only 40 pregnant women.…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings were reported by Shahid et al (29), Uludag et al (25), Okunade et al (8), Kamal et al (13), Bhat and Waheed (31). In Okunade's study, the mean of serum magnesium level was 1.73±0.4 versus 1.93 ± 0.4 mg/dL in the case and control groups, respectively (8).…”
Section: Discussionsupporting
confidence: 81%
“…In their study, Uludag et al reported similar findings and concluded that basal serum magnesium level had a predictive value in evaluating MgSO4 response to tocolysis (25). Other studies suggested that serum magnesium level in pregnancy could be a valuable tool in predicting preterm onset of labor (29,30) and some suggested prophylactic oral magnesium supplementation in women with higher risk for the development of preterm labor (8,14,32).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Since we are trying to introduce a predictive test, all women within the usual age range of the Egyptian pregnant population (16-40 years) were included in our analyses, our study found no signifi cant difference in age, parity, and body mass index between the case and control groups which confi rmed similarities in the two groups used in the study, The incidence of hypomagnesaemia among the healthy parturient used in the study after excluding most of the major risk factors was found to be 36%.This is slightly lower than the incidence of 46% found among similar number of patients studied by [12].…”
Section: Ga At Delivery(wks)contrasting
confidence: 47%